The Effect of Adding Bread Yeast, Tempeh Yeast, and Tape Yeast on The Process of Making VCO from Coconut - Sinaga, Alexander Maruli Tua; Permadi, Adi; Sulistiawati, Endah; Totok Eka Suharto (Universitas Ahmad Dahlan, 2024)
Coconut (Cocos nucifera L.) is one of Indonesia's agricultural products with potential. The most valuable coconut product is coconut oil, which can be obtained from the flesh of fresh coconuts or from copra. Virgin Coconut Oil (VCO) or pure coconut oil is the result of processing from the coconut plant in the form of a clear liquid with a distinctive coconut smell and has a long shelf life. Pure coconut oil or VCO has many benefits for body health, such as natural antibacterial, antiviral, anti-fungal and anti-protozoal properties. This study aims to compare the effect of tempe yeast, bread yeast, tape yeast, and without yeast on variations in the ratio of grated coconut and water (1: 1; 1:1,5; 1:2), on the amount of VCO produced. The experiment was carried out again and then the average volume of VCO produced by each yeast was taken. The average VCO results obtained ratio 1:1 were 209.5 ml for adding bread yeast, 153.5 ml for not using yeast, and 150.5 ml for adding tempeh yeast. Meanwhile, adding tape yeast produce the smallest yield 89 ml . Based on the ratio of grated coconut and water (1 kg: 1 liter) the optimum yield is 1:1. While the minimum yield is 1:1,5 ratio. The most VCO obtained is by adding baker's yeast to thick coconut milk in the second fermentation process. The order of highest yield based on the addition of yeast is bread yeast, tempeh yeast, and tape yeast. The yield of VCO yeast tempeh was slightly better than the yield without adding yeast. The organoleptic results and some of the VCO test results based on SNI 7783-2008 have fulfilled the specified requirements.